Influence of English on Indian Women Writers : Voices from Regional Languages - Rani, K. Suneetha Professor (Sage Publications Pvt. Ltd, 2017)
This book reveals the impact of English not only as a language but also as medium, culture, politics, lifestyle, writing and social change in the context of Indian women.